Association between forest resources and water availability: temporal analysis of the Serra Azul stream sub-basin - DÉBORA J. DUTRA; MARCOS A.T. ELMIRO; SÓNIA M.C. RIBEIRO (Anais da Academia Brasileira de Ciências, 2022)
Abstract Vegetation is expected to influence processes in the water cycle through its structural effects on key ecosystem functions in watersheds. However tropical forests are being submitted to anthropogenic pressures that result in great disturbances in the functioning of ecosystem services. Thus, the present study uses a landscape scale analysis for exploring the associations between land use changes and water availability in the Serra Azul stream watershed. The land use transitions from years 2013 to 2018 were investigated and a set of robust landscape metrics were analyzed across the study region, including water bodies Permanent Preservation Areas. A correlation analysis between the water volume of the Serra Azul reservoir and the landscape metrics was also performed to verify the association between forest resources and water availability. The results show that the region has been submitted to several impacts associated with the loss of forest areas resulting from landscape transformations throughout the region. Forest fragmentation associated to loss of connectivity severely limit water resources availability besides reducing the basin environmental resilience. The role of different management instruments for water resources protection was also discussed, emphasizing the need for participation of stakeholder in the creation process of these environmental protection instruments.